PENGARUH CITA RASA TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA PADA LOYALITAS PELANGGAN PADA RUMAH MAKAN MINANG RAYA GUNUNG PUTRI - Alfian, Faizal Yusuf (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2025)
This study aims to determine and analyze the effect of taste on customer satisfaction and its impact on customer loyalty. The population in this study were all customers of the Minang Raya Restaurant, Gunung Putri, Bogor Regency. The research sample is 100 customers. The Sampling method used is Non-Probabability Sampling and the Sampling Technique used is Purposive Sampling. The data collection method uses the survey method with the data collection instrument in the form of a questionnaire. Furthermore, the data was processed using SmartPLS version 3 and the Data Analysis Method with PLS-SEM. Finally, the results of this study conclude that taste has a significant effect on customer satisfaction; Customer Satisfaction has a significant effect on Customer Loyalty, and Taste has a significant effect on Customer Loyalty. Then, Customer Satisfaction mediates (ie Partial Mediation in the form of Complementary Mediation) the effect of Taste on Customer Loyalty.